A FUZZY LOGIC-BASED MODEL FOR ANALYSIS AND EVALUATION OF SERVICES IN A MANUFACTURING COMPANY - Oblak, Leon; Kitek Kuzman, Manja; Grošelj, Petra (Journal of Applied Engineering Science, 2017)
In an increasingly competitive market, companies must look for new ways to gain competitive advantage. One of these ways is the provision of services. This article presents a multicriteria model for analysis and evaluation of services in a manufacturing company. We divided the services that the manufacturing company can offer to its customers into pre-sales, sales and after-sales services. In the second phase we developed a specific model for the furniture industry. The model was tested with information obtained in a survey by eight kitchen manufacturers from four European countries and was applied to determine the level of services offered. Results have shown that the model can be a useful tool when evaluating the competitiveness of individual manufacturing companies in terms of service provision. Based on the results, companies can develop their business strategies to meet the needs and expectations of potential customers from this perspective as well.
Keywords: Manufacturing company; Customer; Services; Service economy; Product